Estrategias Para Incentivar la Implementación de los Impuestos Ambientales en Empresas Manufactureras de la Ciudad de Duitama (2020)
This article is going to carry out an analysis of environmental taxes to be applied in companies in the manufacturing sector of the city of Duitama, where there are 5 environmental taxes, among which we find forest use, utilization of water and specific discharges, transfer of the electricity sector, the over-tax on tolls, the carbon tax and the tax on the use of plastic bags, which are regulated by Law 99 of 2013 and tax reform 1819 of 2016. These taxes are the basis for companies in this sector to begin to become aware of the environmental deterioration caused over the years and thus find the most appropriate strategies to make the implementation of said taxes effective.